A method for preparing nano whisker reinforced reaction sintered silicon carbide ceramics
By generating ceramic nanowhiskers in situ in silicon carbide ceramic materials, the problems of brittleness of reactive sintered silicon carbide ceramic materials and poor dispersion of external nanowhisker reinforcement bodies are solved, and the toughening of the material and simplification of the process are achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202411972259.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The brittleness of the reactive sintered silicon carbide ceramic material is too high, has low toughness, and is prone to brittle fracture. The nanowhisker reinforcement body added externally is not easily dispersed, and it is easy to be mechanically damaged during the dispersion process, resulting in defects inside the material.
A preparation method is adopted to mix silicon carbide powder, carbon black and ceramic precursor resin waste, add binder, dispersant and water, and stir to obtain a slurry. After molding, it is heated and sintered under a flowing argon atmosphere to generate ceramic nanowhiskers in situ, enhancing the toughness of the reacted sintered silicon carbide ceramic.
The toughening of the reactive sintered silicon carbide ceramics is achieved, which improves the preparation efficiency and cost-effectiveness of the material, simplifies the process, and is suitable for large-scale promotion and application.
Smart Images

Figure CN119751105A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of silicon carbide ceramic preparation, and in particular to a method for preparing nano whisker reinforced reaction sintered silicon carbide ceramic. Background Art
[0002] Silicon carbide ceramics have good mechanical properties, such as high hardness and rigidity, and wear resistance. They are used in precision bearings, compression cylinders, wear-resistant seals, etc. Among the current mainstream processes for preparing silicon carbide ceramics, the preparation technology through reaction sintering has the advantages of simple process, low sintering temperature, short sintering time, and the ability to achieve net size sintering. The reaction sintered silicon carbide materials are widely used in high-tech fields such as aerospace, high-temperature structural parts, and wear-resistant components.
[0003] At present, the reaction sintering process of silicon carbide ceramics generally includes: mixing silicon carbide powder, carbon powder and binder to form a slurry, then sintering, drying, debinding, and finally siliconization. However, the application of reaction-sintered silicon carbide ceramics is mainly limited by its defects of excessive brittleness and low toughness. Brittle fracture is prone to occur during the application process, causing material damage. At present, the main solutions to this defect include: introducing nano whiskers or fibers into reaction-sintered silicon carbide ceramics to toughen them, and through mechanisms such as fiber breakage, fiber debonding, fiber pull-out, crack bridging and crack deflection, the energy loss of the internal stress of the ceramic material is achieved, thereby achieving the improvement of the toughness of the ceramic material. However, the externally added whisker reinforcement is not easy to disperse, and is easily mechanically damaged during the dispersion process, resulting in defects in the material and affecting the performance of the material. Summary of the invention
[0004] In view of this, the present invention provides a method for preparing nanowhisker reinforced reaction sintered silicon carbide ceramics. The preparation method of the present invention can be used to generate ceramic nanowhiskers in situ, and the toughening of the reaction sintered silicon carbide ceramics can be achieved through the stress loss mechanism inside the material. At the same time, the process is simplified, which is suitable for large-scale promotion and application.
[0005] The present invention provides a method for preparing nano whisker reinforced reaction sintered silicon carbide ceramics, comprising the following steps:
[0006] 55-75wt% of silicon carbide powder and 10-20wt% of carbon black are ball-milled and mixed, and then 15-35wt% of ceramic precursor resin waste is added, and then a binder, a dispersant and water are added, and the mixture is stirred and mixed to obtain a slurry; the slurry is formed by a mold, and a porous ceramic body is obtained by demolding;
[0007] The porous ceramic green body is buried with silicon powder, heated to 1300-1500° C. in a flowing argon atmosphere, and kept warm so that the ceramic precursor is sintered in the atmosphere to generate ceramic nano whiskers in situ, thereby obtaining a nano whisker-reinforced SiC / C porous ceramic preform; then the temperature is raised to 1600-1700° C., the vacuum degree is maintained at 1-30 Pa, and the temperature is kept in a vacuum, and the nano whisker-reinforced reaction-sintered silicon carbide ceramic is obtained after cooling.
[0008] In order to overcome the defects of the prior art or solve the above-mentioned technical problems, the purpose of the embodiments of the present invention is to provide a technology for preparing reinforced silicon carbide ceramic materials with simple process, low cost and easy process control. The embodiments of the present invention use the ceramic precursor resin waste generated in the production process of ceramic-based composite materials as one of the raw materials. While saving costs, the resin viscosity is used to improve the stability of the ceramic slurry during the slip injection molding process and the initial strength of the ceramic body after drying and curing. In addition, the present invention generates ceramic nanowhiskers in situ through a one-step method combining atmosphere sintering and reactive infiltration to obtain nanowhisker-reinforced reaction-sintered silicon carbide ceramics. The preparation efficiency of the reinforced ceramic material described in the present invention is significantly improved, and at the same time, the reinforcement and toughening of the reaction-sintered silicon carbide ceramics are achieved.
[0009] In the process of preparing ceramic matrix composites using the impregnation pyrolysis method (PIP method), a large amount of ceramic precursor resin waste is generated, and the treatment and reuse of the waste is also a major problem at present. After extensive research on ceramic precursor resins, the ceramic precursor resin in the embodiment of the present invention can generate ceramic nano whiskers in situ under the catalytic action at high temperature, thereby providing a theoretical basis for the preparation of nano whiskers enhanced by reaction sintering of silicon carbide ceramics by in situ generation of ceramic precursor waste.
[0010] The embodiment of the present invention uses 55-75wt% of silicon carbide powder, 10-20wt% of carbon black and 15-35wt% of ceramic precursor resin waste as main raw materials; specifically, the mass ratio of the ceramic precursor resin waste can be 17-30%, preferably composed of one or more of polycarbosilane, polysiloxane, polynitrogen silane and polymethylsilane, and comes from the waste left over from the preparation of ceramic-based composite materials by impregnation pyrolysis method, mainly ceramic precursor resin, and there is no special restriction on its resin viscosity.
[0011] In an embodiment of the present invention, the purity of the silicon carbide powder is above 85%, preferably 85-99.9%; the mass ratio of the silicon carbide powder is preferably 60-70%. The purity of the carbon black can be above 95%, preferably 95-99.9%.
[0012] In addition, the silicon carbide powder, carbon black, binder, etc. are all commercially available. In an embodiment of the present invention, the particle size of the silicon carbide powder is 5 to 40 μm, and the particle size of the carbon black is 1 to 20 μm. In an embodiment of the present invention, the silicon carbide powder and carbon black are first ball-milled and mixed, and the ball-milling time is preferably 2 to 4 hours to fully mix them.
[0013] In the embodiment of the present invention, the ball-milled raw materials and ceramic precursor resin waste can be placed in a stirring tank, preferably 1 to 5 wt% of a binder and 1 to 5 wt% of a dispersant are added, water is added thereto, and the mixture is stirred and mixed to obtain a slurry.
[0014] In an embodiment of the present invention, the binder is one or more of hydroxymethyl cellulose salt and hydroxyethyl cellulose, preferably sodium carboxymethyl cellulose or hydroxyethyl cellulose.
[0015] In an embodiment of the present invention, the dispersant is one or more of ethanol, methylpentanol, polyethylene glycol and fatty acid polyethylene glycol ester, preferably ethanol or polyethylene glycol, which is beneficial to stabilize the slurry, etc.
[0016] In an embodiment of the present invention, the water is usually deionized water, and its usage is 80-100% of the total weight of silicon carbide powder, carbon black and ceramic precursor resin waste; the stirring and mixing time is 30-60 minutes to obtain a uniformly mixed slurry.
[0017] In the embodiment of the present invention, the obtained slurry is injected into a mold for molding, and a porous ceramic body is obtained by demolding. In the embodiment of the present invention, the injection mold molding includes: pouring the slurry into the mold and letting it stand for 7 to 9 hours, preferably 8 hours, and freeze drying or blast drying for 24 hours. In addition, the present invention has no special restrictions on the slurry injection and mold structure.
[0018] After obtaining the porous ceramic body, in a specific embodiment of the present invention, silicon powder of the same weight as the porous ceramic body is weighed, poured into a graphite crucible and spread, the porous ceramic body is placed on the spread silicon powder, and then the silicon powder of the same weight is weighed and spread on the porous ceramic body so that the porous ceramic body is buried in the silicon powder; the graphite crucible is placed in a vacuum carbon tube furnace, the air inlet valve and the exhaust valve are opened, the temperature is raised to 1300-1500° C. in a flowing argon atmosphere, and the temperature is kept high so that the ceramic precursor is sintered in the atmosphere to generate ceramic nanowhiskers in situ, thereby obtaining a nanowhisker-reinforced SiC / C porous ceramic preform.
[0019] In an embodiment of the present invention, the porous ceramic body is buried with silicon powder (conventional purity and particle size product) twice its weight; the holding time in the argon atmosphere is 2 to 10 hours, further 2 to 6 hours. For example, the temperature in the argon atmosphere can be raised to 1350°C, 1400°C, 1450°C, 1500°C (which is the atmosphere sintering temperature).
[0020] After the insulation is completed in the specific embodiment of the present invention, the air inlet valve and the exhaust valve are closed, the vacuum valve and the vacuum pump are opened, the vacuum degree in the carbon tube furnace is maintained at 1-30 Pa, the temperature is raised to 1650-1750° C., and vacuum insulation is performed. In the embodiment of the present invention, the vacuum insulation time is 30-120 minutes, preferably 30-70 minutes; after the vacuum insulation is completed, the furnace is naturally cooled to obtain nano whisker reinforced reaction sintered silicon carbide ceramics.
[0021] The nano whisker reinforced reaction sintered silicon carbide ceramic prepared by the preparation method of the embodiment of the present invention has a fracture toughness greater than 4.3 MPa·m 1 / 2 .
[0022] The process of the present invention is simple, low-cost and easy to control. The ceramic precursor resin waste generated in the production process of ceramic-based composite materials is used as raw material, which saves costs. In addition, the present invention utilizes the viscosity of the resin to improve the stability of the ceramic slurry during the slip injection molding process and the initial strength of the ceramic body after drying and curing. The ceramic nano whiskers are generated in situ by a one-step method combining atmosphere sintering and reactive infiltration, and nano whisker-reinforced reaction-sintered silicon carbide ceramics are obtained. The present invention improves the preparation efficiency of the material, reduces the cost, and obtains a reinforced and toughened reaction-sintered silicon carbide ceramic material, which is convenient for application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention or the core of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings under the premise of continuous creative work.
[0024] Figure 1 XRD diagram of nano whisker reinforced SiC / C porous ceramic preform prepared for the implementation of the present invention;
[0025] Figure 2 SEM image of the nanowhisker reinforced SiC / C porous ceramic preform prepared for the implementation of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those skilled in the art generally understand. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0027] In order to better understand the present invention, the content of the present invention is further explained in conjunction with the following examples, but the content of the present invention is not limited to the following examples. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commercially available products or products that can be prepared by recognized methods, and the material sample testing is carried out according to the national standard method.
[0028] In the following examples, the ceramic precursor resin waste used is composed of one or more of polycarbosilane, polysiloxane, polynitrosilane and polymethylsilane, and is derived from the waste left over from preparing ceramic-based composite materials by impregnation pyrolysis method.
[0029] Example 1
[0030] The method for preparing nano whisker reinforced reaction sintered silicon carbide ceramics comprises the following steps:
[0031] Step 1: Using 70wt% of silicon carbide powder, 10wt% of carbon black and 20wt% of ceramic precursor resin waste as main raw materials, ball-milling the silicon carbide powder and carbon black for 3h to fully mix them, placing the ball-milled raw materials and ceramic precursor resin waste in a stirring tank, adding 3wt% of the total weight of the main raw materials, a binder and a dispersant of 3wt% of the total weight of the main raw materials, and then adding 100% of the total weight of the main raw materials, deionized water, and stirring for 30min to obtain a slurry;
[0032] Step 2: pour the obtained slurry into a mold, let it stand for 8 hours, dry it with air blast for 24 hours, and demold it to obtain a porous ceramic body;
[0033] Step 3, weighing silicon powder of the same weight as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing silicon powder of the same weight and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder; placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1400° C. in a flowing argon atmosphere, and keeping warm for 3 hours;
[0034] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 10Pa, heat to 1700°C, and keep warm for 60 minutes. After the insulation is completed, cool naturally to obtain nano whisker reinforced reaction sintered silicon carbide ceramic material.
[0035] The purity of the silicon carbide powder is 95% and the particle size is 5 μm, the purity of the carbon black is 98% and the particle size is 15 μm, the ceramic precursor resin waste is polysiloxane, the binder is sodium hydroxymethyl cellulose, and the dispersant is polyethylene glycol.
[0036] The flexural strength of the nanowhisker-reinforced reaction-sintered silicon carbide ceramics is 396 MPa and the fracture toughness is 5.3 MPa·m 1 / 2 .
[0037] Example 2
[0038] The same as Example 1, the only difference is that the ceramic precursor resin waste is polycarbosilane. The bending strength of the prepared nano whisker reinforced reaction sintered silicon carbide ceramic is 406MPa, and the fracture toughness is 5.1MPa·m 1 / 2 Different resin wastes have a certain hardness effect at the same sintering temperature.
[0039] Example 3
[0040] The same as Example 1, the only difference is that the atmosphere sintering temperature is 1350°C. The bending strength of the prepared nano whisker reinforced reaction sintered silicon carbide ceramic is 418MPa, and the fracture toughness is 5.5MPa·m 1 / 2 .
[0041] Example 4
[0042] Step 1: With 65wt% of silicon carbide powder, 18wt% of carbon black and 17wt% of ceramic precursor resin waste as main raw materials, the silicon carbide powder and carbon black are ball-milled for 3h to be fully mixed, the ball-milled raw materials and the ceramic precursor resin waste are placed in a stirring tank, 1wt% of the total weight of the main raw materials as a binder and 2wt% of the total weight of the main raw materials as a dispersant are added, and then 90% of the total weight of the main raw materials as deionized water is added thereto, and stirring is continued for 45min to obtain a slurry;
[0043] Step 2: pour the obtained slurry into a mold, let it stand for 8 hours, dry it with air blast for 24 hours, and demold it to obtain a porous ceramic body;
[0044] Step 3, weighing silicon powder of the same weight as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing the same weight of silicon powder and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder; placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1350° C. in a flowing argon atmosphere, and keeping warm for 2 hours;
[0045] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 15Pa, heat to 1680°C, and keep warm for 30 minutes. After the insulation is completed, cool naturally to obtain nano whisker reinforced reaction sintered silicon carbide ceramic material.
[0046] The purity of the silicon carbide powder is 98% and the particle size is 15 μm, the purity of the carbon black is 99% and the particle size is 5 μm, the ceramic precursor resin waste is polysiloxane, the binder is hydroxyethyl cellulose, and the dispersant is ethanol.
[0047] The flexural strength of the nanowhisker-reinforced reaction-sintered silicon carbide ceramics is 375 MPa and the fracture toughness is 4.8 MPa·m 1 / 2 .
[0048] Example 5
[0049] The same as Example 4, the only difference is that the atmosphere sintering temperature is 1400°C and the ceramic precursor resin waste is polysilazane. The bending strength of the prepared nano whisker reinforced reaction sintered silicon carbide ceramic is 356MPa and the fracture toughness is 4.4MPa·m 1 / 2 .
[0050] Example 6
[0051] The same as Example 4, the only difference is that the atmosphere sintering temperature is 1500°C and the ceramic precursor resin waste is polymethylsilane. The bending strength of the prepared nano whisker reinforced reaction sintered silicon carbide ceramic is 383MPa and the fracture toughness is 5.0MPa·m 1 / 2 .
[0052] The examples show that the reaction-bonded silicon carbide ceramics can be strengthened and toughened by changing the type of ceramic precursor resin and slightly changing the temperature.
[0053] Example 7
[0054] Step 1: Using 60wt% of silicon carbide powder, 15wt% of carbon black and 25wt% of ceramic precursor resin waste as main raw materials, ball-milling the silicon carbide powder and carbon black for 3h to fully mix them, placing the ball-milled raw materials and ceramic precursor resin waste in a stirring tank, adding 5wt% of the total weight of the main raw materials, a binder and 3wt% of the total weight of the main raw materials, and then adding 100% of the total weight of the main raw materials, deionized water, and stirring for 60min to obtain a slurry;
[0055] Step 2: pour the obtained slurry into a mold, let it stand for 8 hours, dry it with air blast for 24 hours, and demold it to obtain a porous ceramic body;
[0056] Step 3, weighing silicon powder of the same weight as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing the same weight of silicon powder and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder; placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1450° C. in a flowing argon atmosphere, and keeping warm for 4 hours;
[0057] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 20Pa, heat to 1740°C, and keep warm for 45 minutes. After the insulation is completed, cool naturally to obtain the nano whisker reinforced reaction sintered silicon carbide ceramic material.
[0058] The purity of the silicon carbide powder is 99% and the particle size is 20 μm, the purity of the carbon black is 99% and the particle size is 10 μm, the ceramic precursor resin waste is polymethylsilane, the binder is sodium hydroxymethylcellulose, and the dispersant is ethanol.
[0059] The flexural strength of the nanowhisker-reinforced reaction-sintered silicon carbide ceramics is 387 MPa and the fracture toughness is 4.5 MPa·m 1 / 2 .
[0060] Example 8
[0061] The same as Example 7, except that the atmosphere sintering temperature is 1300°C, and the ceramic precursor resin waste is a mixture of polysilazane and polycarbosilane. The flexural strength of the prepared nano whisker reinforced reaction sintered silicon carbide ceramic is 392 MPa, and the fracture toughness is 5.1 MPa·m 1 / 2 .
[0062] Example 9
[0063] The same as Example 7, the only difference is that the ceramic precursor resin waste is a mixture of polycarbosilane and polymethylsilane. The bending strength of the prepared nano whisker reinforced reaction sintered silicon carbide ceramic is 408MPa, and the fracture toughness is 5.2MPa·m 1 / 2 .
[0064] Figure 1 The X-ray diffraction spectrum of the SiC nanowhisker reinforced SiC / C porous ceramic preform prepared by adding a polycarbosilane precursor and heat treating it at 1400°C shows that after heat treatment, the polycarbosilane precursor is converted into SiC with strong crystallinity, and the heat treatment has no effect on the original SiC and C components.
[0065] Figure 2The scanning electron microscope image of the SiC nanowhisker reinforced SiC / C porous ceramic preform prepared by adding a polycarbosilane precursor and heat treating at 1400°C in the implementation of the present invention shows that after the heat treatment, the polycarbosilane precursor forms SiC whiskers in the porous ceramic preform, and has no effect on the SiC and C grains, so that the subsequent vacuum reaction infiltration treatment can be carried out normally.
[0066] It can be seen from the above embodiments that the preparation method of the embodiment of the present invention has a simple process and is easy to control. The characteristic of being able to generate ceramic nanowhiskers in situ under sintering in a ceramic precursor atmosphere is combined with a one-step method to form a reaction-sintered silicon carbide ceramic reinforced with nanowhiskers, which not only improves the preparation efficiency of the material and reduces the cost, but also achieves the enhancement and toughening of the reaction-sintered silicon carbide ceramic, and is suitable for large-scale promotion.
[0067] It should be noted that, for those skilled in the art, several improvements and modifications may be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing nano whisker reinforced reaction sintered silicon carbide ceramics, characterized in that: The following steps are involved: 55-75wt% of silicon carbide powder and 10-20wt% of carbon black are ball-milled and mixed, and then 15-35wt% of ceramic precursor resin waste is added, and then a binder, a dispersant and water are added, and the mixture is stirred to obtain a slurry; the slurry is injected into a mold for molding, and a porous ceramic body is obtained by demolding; The porous ceramic green body is buried with silicon powder, heated to 1300-1500° C. in a flowing argon atmosphere, and kept warm so that the ceramic precursor is sintered in the atmosphere to generate ceramic nano whiskers in situ, thereby obtaining a nano whisker-reinforced SiC / C porous ceramic preform; then the temperature is raised to 1600-1700° C., the vacuum degree is maintained at 1-30 Pa, and the temperature is kept in a vacuum, and the nano whisker-reinforced reaction-sintered silicon carbide ceramic is obtained after cooling.
2. The method according to claim 1, characterized in that The ceramic precursor resin waste material is composed of one or more of polycarbosilane, polysiloxane, polynitrosilane and polymethylsilane, and is derived from the waste material remaining in the preparation of ceramic-based composite materials by an impregnation and cracking method.
3. The method according to claim 1, characterized in that The purity of the silicon carbide powder is above 85%; the purity of the carbon black is above 95%.
4. The method according to claim 3, characterized in that The particle size of the silicon carbide powder is 5 to 40 μm, the particle size of the carbon black is 1 to 20 μm; and the ball milling time is 2 to 4 hours.
5. The method according to any one of claims 1 to 4, characterized in that: The binder is one or more of hydroxymethyl cellulose salt and hydroxyethyl cellulose.
6. The method according to any one of claims 1 to 4, characterized in that: The dispersant is one or more of ethanol, methylpentanol, polyethylene glycol and fatty acid polyethylene glycol ester.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The amount of water used is 80-100% of the total weight of silicon carbide powder, carbon black and ceramic precursor resin waste; the stirring and mixing time is 30-60 minutes.
8. The method according to claim 7, characterized in that The injection mold forming comprises: pouring the slurry into a mold, leaving it to stand for 7 to 9 hours, and freeze drying or forced air drying for 24 hours.
9. The method according to claim 8, characterized in that The porous ceramic body is buried with silicon powder twice its weight; the heat preservation time in the argon atmosphere is 2 to 10 hours.
10. The method according to claim 9, characterized in that The vacuum heat preservation time is 30 to 120 minutes, followed by natural cooling to obtain nano whisker reinforced reaction sintered silicon carbide ceramics.
Citation Information
Patent Citations
Carbon fibre enhanced reaction sintering silicon carbide ceramic and preparation method thereof
CN101104559A
Preparation method of SiCf / SiC ceramic matrix composite turbine blades
CN103113123A
Inner heater protection tube made of silicon carbide ceramic composite material and preparation method thereof
CN103833402A
Method of sintering high-toughness silicon carbide ceramic by using vacuum reaction
CN105367058A
A method of preparing a reactive-sintered silicon carbide ceramic product
CN106915966A
Cited By
Cellulose nanocrystal-based ceramic material and preparation method thereof
CN121135468A